Analysis of Male Principal's Leadership Style on Early Childhood Education - Karsa, Dede; Agustin, Mubiar (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Male leadership style will be different with the leadership style of women if they lead the Early Childhood Education. Currently almost 96.86% of Early Childhood Education in West Java is led by women. Researchers are interested in conducting case studies of early childhood education led by men, one of them is in RA Al Qomary Sumedang. The purpose of this research is to describe; 1) what is the objective condition of the male headmaster's leadership style in accepting criticism, opinions and suggestions from employees and teachers, 2) how the male headmaster's leadership style in the process involves his subordinates in making a decision, 3) What is the head leadership style male schools in an effort to help teachers and other employees, 4) What is the male school principal's leadership style in creating a healthy and pleasant atmosphere. The study used a qualitative approach with a case study method in RA Al-Qomary, Wado Sumedang. The results of this study indicate that 1) Male school principals in PAUD are more open and accept all criticism and suggestions from their subordinates. 2) male principals in PAUD in making decisions do not involve too many subordinates, so it is faster in taking decree, messenger 3) male principals have a high concern in helping teachers and other employees, 4) male principals are very good at creating a healthy and pleasant family atmosphere in PAUD. The final conclusion of this study is that male principals have their own advantages and uniqueness in leading early childhood education